Profile of the Kindai Limpuar Gambut Market in Banjar Regency - Nur Laili As Syifa; Mutiani Mutiani; Sigit Triyono; Fatwa Nur’aini; Sovia Husni Rahmia (Universitas Lambung Mangkurat, 2025)
The existence of a market is very important for society. The public understands that there are two market concepts, the traditional market concept and the modern market concept. The existence of traditional markets is still of interest to the public because humans have carried out buying and selling activities since they came to know civilization as a form of fulfilling their needs. One of them, the Kindai Limpuar Gambut Market in Banjar Regency, occurs every day and is still happening today. Therefore, this research aims to explain the profile of the Kindai Limpuar Gambut Market as a traditional market in Banjar Regency. Qualitative approach research is used with descriptive methods. The research subjects were the head of the market manager, traders and buyers. Data sources consist of Primary Data and Secondary Data. Data collection techniques use observation, interviews and documentation. Data analysis is data reduction, data presentation, and drawing conclusions. Test the validity of the data based on source triangulation, technical triangulation, and time triangulation. The results of this research are: Based on the results and discussion of the research conducted by the author, it can be concluded that the Kindai Limpuar Gambut Market has been established for a long time since the 1980s and is currently still the people's choice for buying and selling activities. There are three aspects, namely: physical aspects, economic aspects, and social aspects.